Hydrogen peroxide and superoxide anion production during acetic acid-induced yeast programmed cell death - Guaragnella, N; Antonacci, L; Passarella, S; Marra, E; Giannattasio, S (Folia microbiologica, 2007)
Hydrogen peroxide production in yeast cells undergoing programmed cell death in response to acetic acid occurred in the majority of live cells 15 min after death induction and was no longer detectable after 60 min. Superoxide anion production was found later, 60 and 90 min after death induction when cells viability was 60 and 30%, respectively. In cells protected from death due to acid stress adaptation neither hydrogen peroxide nor superoxide anion could be observed after acetic acid treatment. The early production of hydrogen peroxide in cells in which survival was 100% could play a major role in acetic acid-induced programmed cell death signaling. Superoxide anion is assumed to be generated in cells already en route to acetic acid-induced programmed cell death.
Keywords: Saccharomyces cerevisiae; apoptóza; Superoxides; Superoxide Dismutase; katalasa; Acids; superoxiddismutasa; superoxidy; peroxid vodíku; Hydrogen Peroxide; kyselina octová; Apoptosis; Acetic Acid; kyseliny; Catalase